Emotional Freedom Technique (EFT) Therapy on Chronic Kidney Disease (CKD) Patients to Reduce Fatigue - Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi; Ni Luh Gede Desi Meilena; I Gede Juanamasta; R Tri Rahyuning Lestari (Jurnal Keperawatan, 2021)
Introduction: Fatigue is one of the most common symptoms felt by patients who experience Chronic Kidney Disease, the level of fatigue experienced from low to severe. Some management to deal with fatigue has been done a lot, but the results have not been maximized. Emotional Freedom Technique (EFT) is a psychological therapy that can treat many diseases, both physical illness and psychological illness. Objectives: This study aims to determine the effect of EFT therapy on fatigue in CKD patients. Methods: This type of research is a quasi experimental design with a control group pre-post-test Sample divided into twogroups, consisted of 19 people, selected through purposive sampling. Results: The results showed that the p-value in the treatment group = 0,000 means that there is an effect of therapy EFT on health in CKD patients, whereas, in the control group, there is no difference with the p-value = 1,000. Discussion: The change in CKD patients' fatigue level after EFT therapy is due to a combination of techniques that support the effectiveness of EFT therapy. Conclusion: With this study, it is expected that hospitals can carry out EFT therapy to reduce fatigue in CKD patients to help cure patients.